IMPLEMENTASI MANAJEMEN PELAYANAN ADMINISTRASI LITERASI OLEH DUTA BACA CIANJUR DALAM MENINGKATKAN MINAT BACA ANAK TAHUN 2025-2026 - Aria Kharisma Ananda Putra; Sarifudin; Ade Kohar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Literacy is a fundamental foundation for human resource development; however, the national reading interest remains low, even though several regions, including Cianjur Regency, have shown an increase in their reading interest index. Limitations in facilities and suboptimal management of literacy services call for strengthening the role of Duta Baca (Reading Ambassadors) as collaborative and digitally oriented drivers of regional literacy initiatives. This study aims to analyze the implementation of literacy administrative service management by Duta Baca Cianjur in improving children’s reading interest, as well as to identify institutional synergy, service models, and implementation challenges. The research employs a descriptive qualitative approach with an ethnographic method, using in-depth interviews, participatory observation, and documentation, supported by data triangulation to enhance the credibility of the findings. The results indicate that Duta Baca Cianjur plays a strategic role in strengthening and expanding literacy services through structured collaboration with the Cianjur Regency Office of Archives and Libraries (Disarpus).